Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior (Study pada Karyawan Pemerintah Kabupaten Malang) - Widayanti, Rahayu; Farida, Eni (Universitas Brawijaya, Indonesia, 2016)
One of the keys to success in the organization's growth is the ability of organizations in recruiting, developing, and maintain the human resources wh ch the development of employee behavior are taken into account to improve the quality of service provided by the organization. One of the concepts of behavior is the organizational citizenship behavior (OCB), which is defined as a behavior beyond the standards defined by the organization. Some variables which affect the OCB development in the organization are the job satisfaction and organization commitment.On the other side, Malang Regency Government is currently trying to improve the OCB in SOEs (State Owned Enterprises), such as the State Electricity Company (PLN), in order to improve the quality of service to the public.65 employees of Malang regency government has been taken as an object in this study, multiple linear regression approach is used as an analysis method with job satisfaction and organizational commitment are treated as two independent variables, while the OCB itself is treated as the dependent variable. The results showed that both variables have an influence, but job satisfaction is the most dominant variable on OCB.